Four Stages Time Driven Activity Based Costing (4TD-ABC): An Empirical Study - Mahdi Jawad Al-Kawaz, Salah; Hasan Ali Al-Mamouri, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The 4 steps time driven activity-based costing is one of the most important modern strategic techniques in the field of cost accounting and administration. It helps economic units to achieve the goals of cost management by reducing them, taking appropriate decisions, and enhancing competitiveness by achieving customer satisfaction, current and future desires and high production quality. Thus, the current research aims to prepare a sound methodology concerned with determining the cost of the product by applying the (4TD-ABC) technique in business organizations, which helps them in providing information that will be reflected in the management of costs related to their products. To achieve this goal, the researcher relied upon the application of (4TD-ABC) technique on data obtained by field researcher as well as laboratory records. The results show that the men's clothing factory in Najaf suffers from a lack of features to implement (4TD-ABC) technique, despite all the challenges this laboratory faces, most notably the increase in the intensity of competition. As a result, the application of this technique will help achieve several goals, the most prominent of which is cost management, whether by reducing it or making appropriate decisions or the ability to compete. In addition, the implementation of the (4TD-ABC) technique provides comprehensive and integrated information about resources and their allocation that contribute to increasing the effectiveness of the application of this technique. Therefore, the results confirm that adequate attention is paid to the application of the aforementioned technique for its role in achieving these goals.